Distribution of boron and phosphorus and roles of co-doping in colloidal silicon nanocrystals. (1st October 2019) - Nomoto, Keita; Sugimoto, Hiroshi; Cui, Xiang-Yuan; Ceguerra, Anna V.; Fujii, Minoru; Ringer, Simon P.
Abstract: Boron (B) and phosphorous (P) co-doped colloidal silicon nanocrystals (Si NCs) have unique size-dependent optical properties, which lead to potential applications in optoelectronic and biomedical applications. However, the microstructure of the B and P co-doped colloidal Si NCs – in particular, the exact location of the dopant atoms in real space, has not been studied. A lack of understanding of this underlying question limits our ability to better control sample fabrication, as well as our ability to further develop the optical properties. To study the microstructure, a process enabling atom probe tomography (APT) of colloidal Si NCs was developed. A dispersion of colloidal Si NCs in a SiO2 sol-gel solution and a low temperature curing are demonstrated as the key sample preparation steps. Our APT results demonstrate that a B-rich region exists at the surface of the Si NCs, while P atoms are distributed within the Si NCs. First principles density functional theory calculations of a Si NC embedded in SiO2 matrix reveal that P atoms, which always prefer to reside inside a Si NC, significantly influence the distribution of B atoms. Specifically, P atoms lower the B diffusion barrier at Si/SiO2 interface and stabilize B atoms to reside within individual Si NCs. We propose that the B-modified surface changes the chemical properties of the Si NCs by (i) offering chemical resistance to attack by HF and (ii) enabling dispersibility in solution without aggregation. Graphical abstract: Image 1